Metallothermic reduction of zinc sulfide induced by ball milling - Setoudeh, N.; Welham, Nick (Springer, 2017)
© 2017, Springer Science+Business Media New York. Stoichiometric mixtures of ZnS + Al and ZnS + Mg were milled for different times in a planetary ball mill. The XRD traces of the as-milled samples showed the presence of zinc, MgZn2, and MgS after 30-min milling in the ZnS–Mg system. The traces of MgZn2disappeared after 1-h milling and the reduction reaction seemed to have been completed after 5-h milling. The ZnS–Al system was somewhat different with only slight reduction to zinc after 1 h and ZnS peaks still present after 10 h of milling. Isothermal heating under argon atmosphere of 3-h-milled samples showed the presence of hexagonal ZnAl2S4and mixtures of MgS and Zn0.68Mg0.32S in the ZnS–Al and ZnS–Mg systems, respectively. These results show that the reaction in the ZnS–Al system progressed gradually during milling. The decrease in the crystallite size of reactants materials (especially ZnS) during milling operation led to decrease in the formation temperature of hexagonal ZnAl2S4phase and decrease in the transformation temperature of sphalerite (ZnS) to hexagonal wurtzite.